Tourism in Timor Leste: contributions to a sustainable development - Vong, Manuel Florencio da Canossa (2015)
The main goal of this thesis is to analyse tourism as a contributor to sustainable development, from a supply and demand perspective, in Timor-Leste, a destination not only “young” but also framed in an early stage of touristic development. From the supply side, studies 1 and 2 present a literature review on the concept of sustainable development, in small islands destinations, its weaknesses and vulnerabilities, and whose attractiveness lies in an integrated set of natural resources (attractive beaches, biodiversity, the coral triangle, a rich fauna and flora), its geographic location, tropical climate, socio cultural tradition and a Luso-Timorense cultural mix, that can meet the needs of important segments of the tourist demand. In these studies, the focus is on the residents’ attitudes in relation to sustainable development and, in particular, on the perceptions of local leaders about the importance of the operationalization of the concept. As Timor-Leste is a “young” destination, it is travel industry is still faced with several problems in order to be able to satisfy the demand and to meet the tourists’ motivations, preferences and requirements. In this perspective, the study 3 examines diaspora tourism, while a niche market, allowing for not only the entry of Timor-Leste in the international tourism market, but also an articulation between the people of Timor-Leste in the diasporas and the development of sustainable tourism . In general, the results show that the development of sustainable tourism cannot be successfully implemented without the involvement of all stakeholders such as residents, public sector (local government, policy makers, planners), private sector (tourism operators), and non-governmental organizations (NGOs) that include civil society, religious institutions, the academic community (the supply side), and Timorese diasporas tourists as consumers (the demand side).